Monetary and Nonmonetary Punishment in the Voluntary Contributions Mechanism - Masclet, David; Noussair, Charles; Tucker, Steven; Villeval, Marie-Claire (American Economic Review, 2003)
Monetary and Nonmonetary Punishment in the Voluntary Contributions Mechanism by David Masclet, Charles Noussair, Steven Tucker and Marie-Claire Villeval. Published in volume 93, issue 1, pages 366-380 of American Economic Review, March 2003